Um estudo sobre o vazio educacional no Brasil colonial - Souza, Everton Aparecido Moreira de (2020)
This work will analyze the building, development and deconstruction of Jesuit system education which has had place in colonial Brazil. If we consider that this period is still few explored in the academic field, we see with extremely relevance to study the education in colonial times. For this purpose, in the primary section, we will do a brief historic of creation and development of Jesuitic colleges in Brazil. In the second section, we will show the economic reasons, politicals, religious, philosophical and pedagogical which have motived the Government to choose by extinction of the Jesus Company and consequently the closing of all your colleges in Portugal territory. We will analyze, in the third section, the Pombalinas Reforms in education and will study the Educational Empty in each Brazil's Captaincy. To finalize, we will bring new ideas about the reasons which were subjacent to Educational Empty. This historical itinerary, since the creation of colleges until the Educational Empty, suits to understand the impact that was in the brazilian education the Educational Empty.